Multisensory vs. unisensory learning: how they shape effective connectivity networks subserving unimodal and multimodal integration - Porfyri, Ioanna; Paraskevopoulos, Evangelos; Anagnostopoulou, Alexandra; Styliadis, Charis; Bamidis, Panagiotis D. (Frontiers in Neuroscience, 2025)
The brain synthesizes meaningful interpretations out of the surrounding environment, by integrating sensory input collected by multiple senses. Learning based on contextual multisensory stimulation is considered superior to unisensory. Multisensory methods implemented in rehabilitation and educational studies have demonstrated remarkable neuroplastic changes within cortical networks. However, the exact mechanisms underlying the ensuing neuroplasticity continue to elude comprehension. The present work intends to address this gap at the large-scale level by modeling the experience-induced alterations of multisensory and unisensory training in the effective cortical networks that subserve visual, auditory, and audiovisual information processing. Pre- and post-training EEG analysis demonstrated that the cross-modal training alters significantly the effective connectivity networks in all three modalities, whilst the unisensory methodological approach exerts impact solely on a unisensory (auditory) system. The regions that exhibit most of the alterations are identified within the left medial frontal gyrus (MFG), the left inferior frontal sulcus (IFS), as well as the left insula, areas with renowned multisensory properties. The reconfiguration of the connections following the multisensory training and during the visual and auditory integrative processes concerns mainly higher-order cortical areas, suggesting a top-down process affecting unisensory perception. The results of our study not only strengthen the theory of the superiority of multisensory training compared to unisensory but also indicate that the influence of multimodal training on the unisensory systems succeeds through feedback connections from higher-order association areas, highlighting the complexity of neurophysiological pathways of human perception.